2020
DOI: 10.26434/chemrxiv.13292768.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Modelling Reveals Eight Novel Druggable Binding Sites in SARS-CoV-2’s Spike Protein

Abstract: <p>Spike glycoprotein (S), one of the signature proteins of the SARS-CoV-2, initiates the membrane fusion and virus entry to the host cell. The S protein’s key role in virus viability makes it an attractive candidate for drug design studies. Besides the recent structural characterization of the S protein, information fundamental to drug design such as possible binding sites or molecular fragments with high affinity towards the protein is unknown. We explored the druggability of this protein, focusing on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This suggested linoleate and dexamethasone stabilized the locked S conformation, while cholesterol destabilized it by binding to another site in the hinge region [ 6 ]. Another study of eight putative binding sites on the S protein identified additional ligands that bind to the FABP and stabilize the closed conformation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested linoleate and dexamethasone stabilized the locked S conformation, while cholesterol destabilized it by binding to another site in the hinge region [ 6 ]. Another study of eight putative binding sites on the S protein identified additional ligands that bind to the FABP and stabilize the closed conformation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other very interesting studies, the authors described druggability assessment for the SARS-CoV-2 proteome followed by docking of phytomolecules, the mapping of druggable binding pockets on the experimental structures of 15 SARS-CoV-2 proteins genetic variabilities, a web-based server for navigating possible interactions between SARS-CoV-2 and human proteins, and a web server that predicts the binding modes between SARS-CoV-2 proteins and ligands . In addition to annotated and systematic databases, numerous studies on SARS-CoV-2 potential drug candidate binding sites have been reported. …”
Section: Introductionmentioning
confidence: 99%